2003
DOI: 10.1002/jnr.10599
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of acetylcholinesterase and butyrylcholinesterase changes as a function of the duration of Alzheimer's disease

Abstract: The identification of biochemical markers of Alzheimer's disease (AD) may help in the diagnosis of the disease. Previous studies have shown that Abeta(1-42) is decreased, and tau and phospho-tau are increased in AD cerebrospinal fluid (CSF). Our own studies have identified glycosylated isoforms of acetylcholinesterase (Glyc-AChE) and butyrylcholinesterase (Glyc-BuChE) that are increased in AD CSF. Glyc-AChE is increased in APP (SW) Tg2576 transgenic mice prior to amyloid plaque deposition, which suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…Likewise, the related compound butyrylcholinesterase is differently glycosylated in AD, and both of these cholinesterases have been suggested to be biomarkers for AD [83,84]. The changes in glycosylation of these proteins, however, occur relatively late in the course of disease progression, and are therefore not likely to be early biomarkers [85]. In fact, it has been suggested that both Ab and tau induce the altered glycosylation of the cholinesterases [78].…”
Section: Other Proteins Of Relevance To Admentioning
confidence: 99%
“…Likewise, the related compound butyrylcholinesterase is differently glycosylated in AD, and both of these cholinesterases have been suggested to be biomarkers for AD [83,84]. The changes in glycosylation of these proteins, however, occur relatively late in the course of disease progression, and are therefore not likely to be early biomarkers [85]. In fact, it has been suggested that both Ab and tau induce the altered glycosylation of the cholinesterases [78].…”
Section: Other Proteins Of Relevance To Admentioning
confidence: 99%
“…[85][86][87][88][89][90] Other than in aged nondemented individuals, normal CSF T-tau is found in depression, alcoholic dementia, and in chronic neurological disorders such as Parkinson's disease (PD) and progressive supranuclear palsy. 14,20,50,52,57,63,70,85,88,89,91 Thus, CSF T-tau has a clear clinical diagnostic value in the differentiation between AD and these important and often difficult differential diagnoses.…”
Section: Csf T-taumentioning
confidence: 99%
“…The BCHE gene (3q26) is expressed in many tissues including white adipose tissue, liver, brain and pancreas [5,6] and may have a direct biological impact on the pathogenesis of the amyloidosis related to Alzheimer's disease [7]. Several variants have been identified in BCHE, the most common being a point mutation at nucleotide 1615 (GCA to ACA) predicting an alanine to threonine substitution at codon 539 [8,9].…”
Section: Introductionmentioning
confidence: 99%